2020
DOI: 10.1111/1471-0528.16185
|View full text |Cite
|
Sign up to set email alerts
|

New insights in cerebral findings associated with fetal myelomeningocele: a retrospective cohort study in a single tertiary centre

Abstract: Objective To investigate cerebral anomalies other than Chiari type 2 malformation in fetuses with myelomeningocele (MMC). Design A retrospective cohort study in a single tertiary centre. Setting A review of associated cerebral anomalies in cases with prenatal diagnosis of myelomeningocele. Population Seventy cases of fetal myelomeningocele. Methods Ultrasound and MRI images were blindly reviewed. Postnatal imaging and results of the postmortem results were also reviewed. The association between cerebral anomal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 23 publications
1
22
0
1
Order By: Relevance
“…On the contrary, a small prenatal study, though not in fetuses with SBA, reported a thickened CC as a single abnormal finding in the second trimester, which later becoming normal during the third trimester 29 . We documented a thickened body part of the CC in our cohort, which is in line with the recent publication of Maurice et al 30 . In that study, 18.6% (13/70) of the prenatal cohort of spina bifida fetuses had a thickened CC (>97th centile); although, the authors did not state in which part the CC becomes thickened.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…On the contrary, a small prenatal study, though not in fetuses with SBA, reported a thickened CC as a single abnormal finding in the second trimester, which later becoming normal during the third trimester 29 . We documented a thickened body part of the CC in our cohort, which is in line with the recent publication of Maurice et al 30 . In that study, 18.6% (13/70) of the prenatal cohort of spina bifida fetuses had a thickened CC (>97th centile); although, the authors did not state in which part the CC becomes thickened.…”
Section: Discussionsupporting
confidence: 92%
“…In that study, 18.6% (13/70) of the prenatal cohort of spina bifida fetuses had a thickened CC (>97th centile); although, the authors did not state in which part the CC becomes thickened. In the same study, the authors described a stretched CC in almost 1/10 of their cases (5/70); however, we did not study this feature because of the absence of a clear definition for “stretched.” 30 The thickened appearance of the CC in spina bifida fetuses might change with advancing GA, as the feature was not reported in postnatal studies 14–17 . In this respect, it would be interesting to look at later images or even better to longitudinally follow‐up cases, both in the third trimester and in postnatal life.…”
Section: Discussionmentioning
confidence: 99%
“…In the same publication, the authors also reported abnormalities of cortical development. This comprised perinodular heterotopia (PNH) and abnormal gyral patterning, which were seen in 11 and 3% of MMC cases, respectively 34 …”
Section: Resultsmentioning
confidence: 99%
“…The incidence of ventriculomegaly, defined as lateral ventricular size of ≥10 mm, ranged from 45 to 89% of cases ( Figure 3). 24,[26][27][28][29][30][31][32]34,35 Of those, mild-to-moderate and severe ventriculomegaly were documented in 85 and 15%, respectively. 26 Regarding the shape of the lateral ventricles, an abnormal ultrasound finding was identified in the occipital horns: the normal round shape of the structure was substituted by an abnormal angulated/pointed contour 36,37 (Figure 3).…”
Section: Additional Cranial Ultrasound Findingsmentioning
confidence: 99%
See 1 more Smart Citation